Tumor antigens and vaccines in colorectal cancer - Zhongen Wu; Mengxuan Yang; Yiou Cao (Elsevier, 2022)
Colorectal cancer (CRC) is a common cancer in the world and also has a high death rate. It is reported that vaccination is a great strategy for CRC. CRC vaccines are based on CRC tumor antigens, including tumor-associated antigens like CEA, MUC-1, CTAs and tumor-specific antigens including personalized and shared neoantigen. Challenges emerge in vaccine design and therapeutic effect and combination with other anti-tumor therapies has recently become popular. This review is going to summarize the preclinical and clinical progress of CRC vaccines based on tumor antigens mentioned above, as well as challenges and future in this field.